2020
DOI: 10.3390/ijms21228742
|View full text |Cite
|
Sign up to set email alerts
|

MtPIN1 and MtPIN3 Play Dual Roles in Regulation of Shade Avoidance Response under Different Environments in Medicago truncatula

Abstract: Polar auxin transport mediated by PIN-FORMED (PIN) proteins is critical for plant growth and development. As an environmental cue, shade stimulates hypocotyls, petiole, and stem elongation by inducing auxin synthesis and asymmetric distributions, which is modulated by PIN3,4,7 in Arabidopsis. Here, we characterize the MtPIN1 and MtPIN3, which are the orthologs of PIN3,4,7, in model legume species Medicago truncatula. Under the low Red:Far-Red (R:FR) ratio light, the expression of MtPIN1 and MtPIN3 is induced, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Specifically, low R:FR‐induced auxin biosynthesis enhances PIN3's abundance and lateral localization, which promotes auxin flux to the epidermis. Moreover, loss of function of MtPIN1 and MtPIN3 disrupts shade‐avoidance responses and reduces petiole length in Medicago truncatula (Zhang et al, 2020). Our previous results indicated that clathrin modulates the subcellular localization of PIN3 and auxin maxima during hook formation as well as blue light (BL)‐triggered hypocotyl phototropism in Arabidopsis (Yu et al, 2016; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, low R:FR‐induced auxin biosynthesis enhances PIN3's abundance and lateral localization, which promotes auxin flux to the epidermis. Moreover, loss of function of MtPIN1 and MtPIN3 disrupts shade‐avoidance responses and reduces petiole length in Medicago truncatula (Zhang et al, 2020). Our previous results indicated that clathrin modulates the subcellular localization of PIN3 and auxin maxima during hook formation as well as blue light (BL)‐triggered hypocotyl phototropism in Arabidopsis (Yu et al, 2016; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, PIN3 , which is a member of the PIN family, has rarely been reported to be involved in the establishment of leaf adaxial-abaxial polarity. The leaves of the mtpin1/mtpin3 double mutant displayed an abnormal abaxial surface only in Medicago truncatula ( Zhang et al., 2020 ). In our study, BpPIN3 suppressed expression transgenic lines (RE lines) showed leaf rolling; however, this phenotype was distinct from that of the mtpin1/mtpin3 double mutant in that the adaxial showed an upward rolling ( Figure 2C ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of most PINs was up-regulated compared with full light conditions, and those in group VI (PIN3/4/7) showed the same response trend ( Figure 9 a). PIN3/4/7 subgroups such as A. thaliana AtPIN3 and Medicago truncatula MtPIN3 were also found to be involved in plant shading responses [ 66 , 67 ], so it was further speculated that the M. micrantha PINs may promote the rapid elongation of the stem under low light by regulating the auxin level of the stem. Similarly, under defoliation stress, M. micrantha maintained stem growth by improving the photosynthesis rate and increasing the amount of auxin and other phytohormones [ 35 ].…”
Section: Discussionmentioning
confidence: 99%